2017
DOI: 10.1371/journal.pone.0188794
|View full text |Cite
|
Sign up to set email alerts
|

Assemblies of amyloid-β30–36 hexamer and its G33V/L34T mutants by replica-exchange molecular dynamics simulation

Abstract: The aggregation of amyloid-β peptides is associated with the pathogenesis of Alzheimer’s disease, in which the 30–36 fragments play an important part as a fiber-forming hydrophobic region. The fibrillar structure of Aβ30–36 has been detected by means of X-ray diffraction, but its oligomeric structural determination, biophysical characterization, and pathological mechanism remain elusive. In this study, we have investigated the structures of Aβ30–36 hexamer as well as its G33V and L34T mutants in explicit water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 78 publications
2
8
0
Order By: Relevance
“…As the side chains of E22 and D23 are oriented to water solution, C 60 (OH) 12 is inclined to form H-bonds with them. Considering the important roles of C-terminal hydrophobic residues in Aβ aggregation and toxicity [41,42,43], it is conceivable that the binding of C 60 and C 60 (OH) 6 molecules to the C-terminal region can prevent Aβ fibrillization. In addition, the C 60 (OH) 6 molecule has higher affinity to bind to elongation surfaces than C 60 and C 60 (OH) 12 , which makes C 60 (OH) 6 a more effective inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…As the side chains of E22 and D23 are oriented to water solution, C 60 (OH) 12 is inclined to form H-bonds with them. Considering the important roles of C-terminal hydrophobic residues in Aβ aggregation and toxicity [41,42,43], it is conceivable that the binding of C 60 and C 60 (OH) 6 molecules to the C-terminal region can prevent Aβ fibrillization. In addition, the C 60 (OH) 6 molecule has higher affinity to bind to elongation surfaces than C 60 and C 60 (OH) 12 , which makes C 60 (OH) 6 a more effective inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…The average intra-chain H-bond number slightly increased with the peak location shifting from eight to 11. Previous MD study on β-amyloid oligomer showed that the disturbance of the inter-peptide H-bonding network and the increment of side-chain H-bonds may result in increased coil content and morphological diversity [76]. The reduction of inter-chain backbone H-bonds of αS protofibril induced by DA/NE molecules is supposed to go against the structural stability of αS protofibril and the subsequent fibrillation.…”
Section: Discussionmentioning
confidence: 97%
“…Molecular dynamic simulations in the absence of a preconceived model can sometimes be informative for relatively small peptides and small assemblies. For example, Sun et al 24 found that in some simulation runs beginning with randomized peptides with the sequence of Aβ 16-22 (the core of S2) a six-stranded antiparallel β-barrel formed, and Qian et al 25 obtained similar results for peptides with a Aβ 30-36 sequence of S3. But these types of simulations last only a fraction of a second, and it is unrealistic to expect them to produce accurate predictions for larger peptides and larger assemblies that form gradually and often depend upon an initial seed structure.…”
Section: Atomic Scale Modeling and Molecular Dynamics Simulationsmentioning
confidence: 94%